Antimicrobial activity of Brazilian propolis extracts for Staphylococcus aureus of sheep and goats mastitis origin - Andrade, NPC (2015)
Twenty-four S. aureus isolates were analysed. From those, 22 were isolated from milk of goats and sheep with clinical and subclinical mastitis, from the region of Vale do São Francisco in the Brazilian Sertão and S. aureus ATCC 25923 plus a MRSA strain were added. Alcoholic extracts were produced from several batches of green, red and brown propolis consisting of 300 g of raw propolis in 700 mL of 70 % ethanol. Four genes related to antimicrobial resistance were assessed: blaZ that determines the resistance to β-lactam antibiotics, and genes icaA, icaD and bap that influence the production of biofilm. For the tests of susceptibility to different types of propolis the microdilution method was used, in triplicate, and dilutions between 0.003672 and 15% were tested, 70 % ethanol consisted of a negative control. The gene blaZ was found in 15 isolates; icaA gene was present in 3 isolates, icaD gene in 2 and bap gene was detected in 6 isolates. All the propolis tested exhibited antimicrobial activity, ranging from 44 to 100 % of susceptible isolates depending on different propolis batches. According to the results of this experiment the green and red propolis appear to have better antimicrobial activity than the brown variety.